Analisis Akuntansi Perpajakan Dan Dampak Penerapan PPH Pasal 21 Terhadap Wajib Pajak (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Understanding tax accounting which is based on tax regulation (Pph 21) will influence taxpayer awareness. The purpose of this research is to provide a general overview of research related to tax accounting for taxpayers based on PPH article 21. The methodology used in this research is a literature review study using 20 articles that discuss the topic of tax accounting for taxpayer compliance. based on PPh article 21 which was carried out in the period 2015 – 2023 with empirical and academic studies. The results of this research can be concluded that understanding tax accounting in financial management is very necessary because agency financial reporting can have a good effect on the effectiveness of company financial management. Understanding accounting in preparing financial reports is very important to pay attention to. By understanding accounting in preparing reports, effective financial management reports will be created, where in preparing these reports, presenting the agency's financial reports properly and correctly will influence taxpayer compliance.